From Policy to Practice: Understanding the Challenges of Middle Management in Embedding ESG Targets into Daily Operations in the Manufacturing Industry - Shahrizal Bin Kamaruddin; Wahida Binti Ahmad (Fakultas Ekonomi & Bisnis Universitas Paramadina, 2026)
In recent years, manufacturing organizations have increased their dedication to Environmental, Social, and Governance (ESG) objectives as part of their overall sustainability initiatives. Yet, it is difficult to translate these commitments into operational practice. Based on the evidence of recent research from manufacturing firms such as Jeong et al. (2025) on the variation in ESG performance across managerial levels and Barletta et al. (2021) on the importance of organizational readiness as a prerequisite for the implementation of sustainability, this paper takes a narrative and conceptual approach to investigate the role of middle managers in bringing ESG targets to life in day-to-day operations. The abstract is still too descriptive and lengthy, and does not clearly state the research gap and specific theoretical contributions. It is recommended to sharpen the focus on conceptual novelty and explicitly state the article's main contributions to ESG literature and the role of middle management. (2022). Complemented by Corporate Sustainability and the organizational integration perspectives, the literature reveals that although institutional pressures steer firms toward ESG alignment, actual operational embedding depends strongly on internal structures, managerial competence, and organizational readiness. Middle managers are required to translate top-down commitments, to apportion resources, and to balance production needs with sustainability demands in environments that are often marked by workforce complexity and resource constraints. This paper concludes with a conceptual model that shows how institutional forces interact with organizational support ecosystems and middle management capability, offering insights into why ESG integration is deep in some manufacturing firms and shallow in others. The study provides a basis for understanding the ESG implementation gap and directions for future empirical research in the manufacturing sector.